Machine Learning-Based Automated Stroke Prediction: An Explanatory and Investigative Study Using a Web Application for Prevention - Saranya K; Dr. D. Magdalene Delighta Angeline (Utilitas Mathematica, 2025)
Stroke represents a massive international hazard, with profound fitness and financial consequences, Cerebral blood flow is obstructed, leading to neurological impairments. The green prediction systems stress the importance of stroke in persons who are at risk of having one, especially in older people who are getting older. This study addresses the challenges of ironing by enhancing future automated algorithms. These algorithms need to make it easier to intervene early, and they will definitely save lives by predicting strokes.